برصغیر میں عربی ادب کے ترویج کے محرکات: The causes of spreading Arabic literature and language in the Sub-Continent - Ullah, Sibghat; Rana, Dr. Jahanzaib (Journal of Quranic and Social Studies, 2021)
At the time of arrival of Muslim community in sub –continent region and due to their settlement in the region Arabic language has been prevailed and such as the system of its publication and learning has been commenced. Because the directives of Islam and Laws are in the Arabic Language as per Quran and Sunnah So that it is necessary to learn the Arabic Language for the Awareness of Islamic direction .So that to achieve the knowledge of Sharia including the expertise the peoples of subcontinent has been achieved the expertise of Arabic language ,literature ,knowledge ,ilmulSaraf ,al Nahaw ,knowledge of al-Ishteqaq and ilmul Balagha etc. Moreover it is clarify that the scholar of Arab have been convinced their expertise .The Basic point of service in the Arabic language of Scholars of Sub continent that they do not served only to enhanced the language but the cause of service to serve themselves to achieve the better performance of identification of Islam. In this Article I mention the causes of Spreading of Arabic language in Sub continent such as Madaris, Schools and teaching of Arabic language in Universities etc.